The Supreme Court in the Intimate Lives of Americans : Birth, Sex, Marriage, Childrearing, and Death. - Ball, Howard (NYU Press, 2002)
Choice Outstanding Academic Title 2003. Personal rights, such as the right to procreate--or not--and the right to die generate endless debate. This book maps out the legal, political, and ethical issues swirling around personal rights. Howard Ball shows how the Supreme Court has grappled with the right to reproduce and to abort, and takes on the issue of auto-euthanasia and assisted suicide, from Karen Ann Quinlan through Kevorkian and just recently to the Florida case of the woman who was paralyzed by a gunshot from her mother and who had the plug pulled on herself. For the last half of the twe.